Penilaian Kualitas Quality of Service Jaringan Internet WLAN PT. Solid Fintek Indonesia - Rizky, Muhammad; Dwiasnati, Saruni (Universitas Multi Data Palembang, 2024)
This research focuses on analyzing QoS (Quality of Service) on the internet network of PT. Solid Fintek Indonesia. Quality of Service is used as an analysis method to measure the quality of internet network services, the information from which can be input to improve disturbances that often occur on the network of PT. Solid Fintek Indonesia, such as sudden network slowdowns, lag that results in communication disruption, and loss of Wi-Fi network. In this study, the analysis was conducted using QoS parameters, including throughput, delay, jitter, and packet loss. Wireshark was used as a tool to scan and record internet traffic. The main objective of this research is to provide valuable insights for improving the performance of WLAN networks at PT. Solid Fintek Indonesia and similar organizations. By understanding the factors of network quality, it is hoped to find an effective solution to improve performance network. The results of testing the WLAN network based on TIPHON standardization at PT. Solid Fintek Indonesia show an index value on the throughput parameter of 2390 Kbps with the category “Very Good”, delay of 4,13 ms with the category “Very Good”, jitter of 4,13 ms with the category “Good”, and packet loss of 2,67 % with the category “Very Good”.